Appendix 5.1: Letter from Luis Nepomuceno to Imelda Marcos on the Film Maharlika - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies; Vol 27, No 1-2-Vol 28, No 1-2 (2012-2013): Marcos Pa Rin! The Legacy and the Curse of the Marcos Regime, 2017)
Iginuhit ng Tadhana (1964), as Teresita Maceda points out, was the first film about Ferdinand Marcos. It had a sequel, Pinagbuklod ng Langit (1969). Both were campaign films. A third film, Maharlika , was focused on Marcos’s guerilla exploits, which were mostly fabrications (Ariate and Reyes 2016a, 2016b, 2016c). This was the film that brought the infamous Dovie Beams to the Philippines. She was cast as the love interest of the film’s protagonist. While she completed filming her role, over the course of her stay in the Philippines, she also became Ferdinand Marcos’s mistress. A recording she made of one of their trysts became the soundtrack of the opposition. Based on the following letter, Imelda Marcos, understandably, had the film placed under lock and key. However, the custodian’s financial difficulties may have been the reason why the film resurfaced in the 1980s—in time for the dawn of home video. According to a number of websites (e.g., Film Affinity 2017), one title that the film was released under was Guerilla Strike Force . This series of events show Ferdinand and Imelda Marcos’s attempts to control the manufacture of myths about them, which at times required suppression of undesirable events.